A Noninvasive Imaging Technique to Evaluate Therapeutic Efficacy after Injection of n-Butyl-2-cyanoacrylate Tissue Adhesive into Gastric Varices: A Case Report - Bret J Spier; Andrew J Taylor; Patrick R Pfau; Adnan Said; Deepak V Gopal (Canadian Journal of Gastroenterology, 2009)
A novel use of multidetector computed tomographic intravenous (MDCT IV) portography in the evaluation of gastric varices treated with tissue adhesive is described. A 55-year-old man presented with upper gastrointestinal hemorrhage as a result of bleeding gastric varices. The patient was stabilized and the gastric varices were treated with n-butyl-2-cyanoacrylate (two injections, total 7.5 mL). MDCT IV portography performed after injection revealed thrombosis of all but one of the submucosally based gastric varices. The endoscopist who performed repeat endoscopy three weeks later was then able to direct therapy at the remaining patent submucosally based gastric varix. This represents the first reported use of MDCT IV portography in the evaluation of treatment adequacy in a patient with gastric varices treated with n-butyl-2-cyanoacrylate.